2021
DOI: 10.3390/jcm10194299
|View full text |Cite
|
Sign up to set email alerts
|

Age at Natural Menopause and Blood Pressure Traits: Mendelian Randomization Study

Abstract: Observational studies suggest that early onset of menopause is associated with increased risk of hypertension. Whether this association is causal or due to residual confounding and/or reverse causation remains undetermined. We aimed to evaluate the observational and causal association between age at natural menopause (ANM) and blood pressure traits in Caucasian women. A cross-sectional and one-sample Mendelian randomization (MR) study was conducted in 4451 postmenopausal women from the CoLaus and Rotterdam stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Menopause goes hand in hand with 10%–15% higher circulating LDL‐cholesterol and triglyceride levels and a reduction in high‐density lipoprotein (HDL)‐cholesterol 54 . Together with this less favourable lipid profile after menopause, various studies also demonstrated a rise in blood pressure, which may be a direct effect of hormonal changes on the vasculature and metabolic changes related to ageing 55–57 . Endothelial dysfunction starts in early menopause even before signs of subclinical atherosclerosis 58 and while healthy endothelium is sensitive to the vasodilator properties of oestrogens, this reverses when vascular stiffness and atherosclerotic disease develop over time 59 .…”
Section: Sex Hormones and Their Effect On Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Menopause goes hand in hand with 10%–15% higher circulating LDL‐cholesterol and triglyceride levels and a reduction in high‐density lipoprotein (HDL)‐cholesterol 54 . Together with this less favourable lipid profile after menopause, various studies also demonstrated a rise in blood pressure, which may be a direct effect of hormonal changes on the vasculature and metabolic changes related to ageing 55–57 . Endothelial dysfunction starts in early menopause even before signs of subclinical atherosclerosis 58 and while healthy endothelium is sensitive to the vasodilator properties of oestrogens, this reverses when vascular stiffness and atherosclerotic disease develop over time 59 .…”
Section: Sex Hormones and Their Effect On Atherosclerosismentioning
confidence: 99%
“…with this less favourable lipid profile after menopause, various studies also demonstrated a rise in blood pressure, which may be a direct effect of hormonal changes on the vasculature and metabolic changes related to ageing. [55][56][57] Endothelial dysfunction starts in early menopause even before signs of subclinical atherosclerosis 58 and while healthy endothelium is sensitive to the vasodilator properties of oestrogens, this reverses when vascular stiffness and atherosclerotic disease develop over time. 59 All of these detrimental phenomena contribute to an increased rate of MI in women after menopause.…”
Section: Clinical Manifestation and Therapiesmentioning
confidence: 99%
“…This type of study will not be discussed in this review, and readers interested are encouraged to read references [176,177]. However, it should be noted that studies existed usually focusing on how age at menopause affects certain traits, instead of discussing how some traits impact age at menopause [178,179]. Apparently, the later one is what clinicians most care about in order to withstand ovarian aging and is needed to be developed.…”
Section: Genome-wide Association Studymentioning
confidence: 99%
“…However, several studies have demonstrated a positive association between age at menopause and hypertension [6][7][8]. Additionally, a positive association between age at menopause and obesity has been reported [9,10].…”
mentioning
confidence: 99%